2017
DOI: 10.3390/rs9070753
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Reconstruct Overhead High-Voltage Power Lines Using Cable Inspection Robot LiDAR Data

Abstract: Overhead high-voltage power lines are key components of power transmission and their monitoring has a very significant influence on security and reliability of power system. Advanced laser scanning techniques have been widely used to capture three-dimensional (3D) point clouds of power system scenes. Nevertheless, power line corridors are found in increasingly complex environments (e.g., mountains and forests), and the multi-loop structure on the same power line tower raises great challenges to process light d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…This indicates that the forest plantation was the most affected landscape type during and after the construction of HVPTL, whereas bamboo forests and non-forest lands were less affected by the construction of HVPTL. This is in line with a previous finding, which indicated that power lines inevitably cross more forests with the rapid development of the network grid [3]. This, in turn, increases forest fragmentation to a certain degree [7].…”
Section: Edge Habitat Impacts Of the High-voltage Power Transmission supporting
confidence: 93%
See 3 more Smart Citations
“…This indicates that the forest plantation was the most affected landscape type during and after the construction of HVPTL, whereas bamboo forests and non-forest lands were less affected by the construction of HVPTL. This is in line with a previous finding, which indicated that power lines inevitably cross more forests with the rapid development of the network grid [3]. This, in turn, increases forest fragmentation to a certain degree [7].…”
Section: Edge Habitat Impacts Of the High-voltage Power Transmission supporting
confidence: 93%
“…To meet the constantly growing electricity demands and to reduce electricity transmission losses, countries in Europe, North America, and Asia are attempting to develop high-voltage power transmission lines (HVPTLs) including pylons [1,2]. HVPTLs have become globally necessary components of power transmission infrastructure, covering 5.5 million km in 2014, with predictions that this will increase to 6.8 million km in 2020 [3]. Likewise, the development of HVPTL in China is expected to increase, to reduce electricity transmission energy losses, since long distances exist between power stations and end-users [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many monitoring sensors have been designed and put into actual test for transmission line galloping monitoring. The authors in [28] have developed a cable inspection robot to acquire light detection and ranging (LiDAR) data. Also, the authors in [24] have designed a wireless sensor module with smooth spherical structure shell, and it contains an inertial measurement unit and wireless communication components.…”
Section: Transmission Line Galloping Monitoring Systemmentioning
confidence: 99%